Trigonometric Identity Maybe?

Geometry Level 4

I made an elementary trigonometric identity complicated to get this expression.

k = 1 10 ( sin ( 2 π k 11 ) i cos ( 2 π k 11 ) ) \large \sum_{k=1}^{10} \left ( \sin \left ( \frac {2\pi k}{11 } \right ) - i \cos \left ( \frac {2\pi k}{11 } \right ) \right )

What is the value of 4 times the square of the expression above?

Details and Assumptions : i = 1 i =\sqrt {-1} denotes the imaginary unit .

Also try this .


The answer is -4.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Chew-Seong Cheong
Feb 10, 2018

By Euler's formula we have e i x = cos x + i sin x e^{ix} = \cos x + i \sin x . Then

S = k = 1 10 sin ( 2 π k 11 ) i cos ( 2 π k 11 ) = k = 1 10 i e 2 π k 11 = k = 1 10 i ω k where ω = e 2 π 11 is the 11th root of unit. = i ( k = 0 10 ω k 1 ) Note that k = 0 10 ω k = 0 = i \begin{aligned} S & = \sum_{k=1}^{10} \sin \left(\dfrac {2\pi k}{11} \right) - i \cos \left(\dfrac {2\pi k}{11} \right) \\ & = \sum_{k=1}^{10} - i {\color{#3D99F6} e^{\frac {2\pi k}{11}}} = \sum_{\color{#3D99F6}k=1}^{10} - i \color{#3D99F6} \omega^k & \small \color{#3D99F6} \text{where } \omega = e^{\frac {2\pi}{11}} \text{ is the 11th root of unit.} \\ & = -i \left(\sum_{\color{#D61F06}k=0}^{10} \omega^k - 1 \right) & \small \color{#3D99F6} \text{Note that }\sum_{\color{#D61F06}k=0}^{10} \omega^k = 0 \\ & = i \end{aligned}

Therefore 4 S 2 = 4 ( i 2 ) = 4 4S^2 = 4(i^2) = \boxed{-4} .

Small typo: Note thar \text{Note thar}

Bernard Peh - 3 years, 4 months ago

Log in to reply

Thanks, corrected.

Chew-Seong Cheong - 3 years, 4 months ago

@Chew-Seong Cheong , nice solution sir. Also, I am missing your solutions to my problems. I always look forward to see your solutions for my problems.

Hana Wehbi - 3 years, 4 months ago
Nishant Rai
Apr 5, 2015

simpler one. Take -i common from the whole expression and then evaluate sigma from k=0. To compensate for the changes, subtract -1. Once you start the sigma part from k=0 , one can easily see that it is sum of the roots of unity, which is equal to 0. so you are left with only -1 in the bracket. And the expression evaluates to 'i'.

take i -i common, the expression becomes

i ( k = 1 10 c o s ( 2 k π 11 ) + i s i n ( 2 k π 11 ) ) -i (\displaystyle \sum_{k=1}^{10} cos(\frac{2k \pi}{11})+i sin(\frac{2k \pi}{11}))

i k = 1 10 e i 2 k π 11 -i \displaystyle \sum_{k=1}^{10} e^{i \frac{2 k \pi}{11}} ..... ( 1 ) (1)

11 roots of unity 1 , x 1 , x 2 , x 3 . . . . . . x 10 1,x_{1},x_{2},x_{3}......x_{10}

Also 1 + x 1 + x 2 + . . . . x 10 = 0 1+x_{1}+x_{2}+....x_{10}=0

x 1 + x 2 + . . . . x 10 = 1 x_{1}+x_{2}+....x_{10}=-1

in ( 1 ) (1)

i ( x 1 + x 2 + x 3 + . . . . . x 10 ) -i (x_{1}+x_{2}+x_{3}+.....x_{10})

i \boxed{i}

Tanishq Varshney - 6 years, 2 months ago
Jerry Bao
Feb 14, 2018

Think of each part of the sum as a single vector. These vectors form the vertices of a regular hendecagon. But one of the vectors are missing from the sum. This is the case when k=11. Plug k=11 to get -i. Due to the fact that it is a regular hendecagon, the other vectors must cancel out the k=11 vector, so their sum must equal to i.

Squaring and multiplying by 4 gives -4.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...